Comparative Study of the Effect of Macrolide Antibiotics Erythromycin, Clarithromycin, and Azithromycin on the ERG1 Gene Expression in H9c2 Cardiomyoblast Cells - Hajimirzaei, Nima; Khalili, Nazila Pour; Boroumand, Behshad; Safari, Fatemeh; Pourhosseini, Armin; Judi-Chelan, Reza; Tavakoli, Fatemeh (Drug Research, 2020)
Macrolides are clinically well-established class of antibiotics. Macrolides induce cardiotoxicity by blocking ether-a-go-go–related gene (ERG) potassium channels in cardiac myocytes. The aim of this study was to compare the effects of erythromycin, clarithromycin and azithromycin on cell viability and expression of ERG1 gene in H9c2 cells. Cell viability and ERG1 gene expression of H9c2 cells in 3 different concentrations, 1, 10 and 25 µg/ml, after 48 and 72 h were determined by MTT test and Real time-PCR method respectively. After 48 h, the growth of H9c2 cells treated with erythromycin, clarithromycin and Azithromycin (except two doses) were inhibited significantly compared to control group (p<0.05). All three groups of antibiotics showed toxic effects on cells after 72 h in all concentrations. Azithromycin-inhibiting effects were significantly higher than two other groups after 72 h of treatment. The expression of ERG1 gene increased in all three groups of antibiotics by increasing the concentration and duration of treatment. Azithromycin had the most pronounced effect on ERG1 expression in 48 and 72 h. This study indicated that these macrolides affect ERG1 expression due to their potential cardiac adverse effects. Further investigations are required to understand the exact mechanism of cardiotoxicity associated with macrolides.
Keywords: adverse drug reactions; antibacterial drugs; cardiovascular pharmacology; K-channels; molecular pharmacology; toxicology